Price Wars In Malacca Readymixed Concrete Industry - A Bivariate Quantitative Analysis Of Malacca Readymixed Concrete Production And Prices - Keong, Wong Fock (2001)
This study is carried out with the primary objective to analyze the relationship between Malacca readymixed concrete production and its prices.